A role for long-chain acyl-CoA synthetase-4 (ACSL4) in diet-induced phospholipid remodeling and obesity-associated adipocyte dysfunction - Elizabeth A. Killion (Molecular Metabolism, 2018)
Objective: Regulation of fatty acid (FA) metabolism is central to adipocyte dysfunction during diet-induced obesity (DIO). Long-chain acyl-CoA synthetase-4 (ACSL4) has been hypothesized to modulate the metabolic fates of polyunsaturated FA (PUFA), including arachidonic acid (AA), but the in vivo actions of ACSL4 are unknown. The purpose of our studies was to determine the in vivo role of adipocyte ACSL4 in regulating obesity-associated adipocyte dysfunction. Methods: We developed a novel mouse model with adipocyte-specific ablation of ACSL4 (Ad-KO) using loxP Cre recombinase technology. Metabolic phenotyping of Ad-KO mice relative to their floxed littermates (ACSL4floxed) was performed, including body weight and body composition over time; insulin and glucose tolerance tests; and energy expenditure, activity, and food intake in metabolic cages. Adipocytes were isolated for ex vivo adipocyte oxygen consumption by Clark electrode and lipidomics analysis. In vitro adipocyte analysis including oxygen consumption by Seahorse and real-time PCR analysis were performed to confirm our in vivo findings. Results: Ad-KO mice were protected against DIO, adipocyte death, and metabolic dysfunction. Adipocytes from Ad-KO mice fed high-fat diet (HFD) had reduced incorporation of AA into phospholipids (PL), free AA, and levels of the AA lipid peroxidation product 4-hydroxynonenal (4-HNE). Additionally, adipocytes from Ad-KO mice fed HFD had reduced p53 activation and increased adipocyte oxygen consumption (OCR), which we demonstrated are direct effects of 4-HNE on adipocytes in vitro. Conclusion: These studies are the first to elucidate ACSL4's in vivo actions to regulate the incorporation of AA into PL and downstream effects on DIO-associated adipocyte dysfunction. By reducing the incorporation of AA into PL and free fatty acid pools in adipocytes, Ad-KO mice were significantly protected against HFD-induced increases in adipose and liver fat accumulation, adipocyte death, gonadal white adipose tissue (gWAT) inflammation, and insulin resistance (IR). Additionally, deficiency of adipocyte ACSL4 expression in mice fed a HFD resulted in increased gWAT adipocyte OCR and whole body energy expenditure (EE). Keywords: Adipocytes, Fatty acid metabolism, Obesity, Arachidonic acid, Polyunsaturated fatty acid